The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00403-009-0959-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator-activated receptor-γ inhibits transforming growth factor-β1 induction of connective tissue growth factor and extracellular matrix in hypertrophic scar fibroblasts in vitro

Abstract: Peroxisome proliferator-activated receptor-gamma (PPAR-gamma) ligands have been recently reported to have beneficial effects on organ fibrosis. However, their effects on extracellular matrix (ECM) turnover in hypertrophic scar fibroblasts (HSFs), and the related molecular mechanisms are unknown. HSFs were cultured and exposed to different concentration PPAR-gamma ligands in the presence of transforming growth factor-beta1 (TGF-beta1). In growth-arrested HSFs, a PPAR-gamma natural ligand (15-deoxy-D12,14-prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The main reasons to assess the efficacy of new synthetic PPARγ modulators in the treatment of intestinal fibrosis are due to the evidences that: (i) together with the adipose tissue, the intestine represents the main site where PPARγ achieves the higher tissue expression levels and (ii) PPARγ activation downregulates TGFβ/Smad pathway [7,13,24,25,35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons to assess the efficacy of new synthetic PPARγ modulators in the treatment of intestinal fibrosis are due to the evidences that: (i) together with the adipose tissue, the intestine represents the main site where PPARγ achieves the higher tissue expression levels and (ii) PPARγ activation downregulates TGFβ/Smad pathway [7,13,24,25,35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have examined the relationship between inhibition of CTGF and reduction of hypertrophic scars. PPARg activators 15d-PGJ2 and GW7845 were found to attenuate TGF-b1-induced expression of CTGF and collagens at both mRNA and protein levels in hypertrophic scar fibroblasts [34]. These data supported the application of PPARg agonists for treatment of hypertrophic scars through modulating CTGF.…”
Section: Connective Tissue Growth Factor Pathwaymentioning
confidence: 85%
“…Peroxisome proliferator-activated receptor-g (PPARg) ligands15d-PGJ2 and GW7845 inhibited the expression and phosphorylation of TGF-b1/Smads leading to anti-proliferative effect and reduced ECM production in hypertrophic scar fibroblasts [34]. Recently, many natural compounds have increasingly been demonstrated to have anti-hypertrophic scar properties by interrupting TGF-b1 signaling, including botulinum toxin type A [35], tetrandrine [36], baicalein [16], loureirin B [37,38], and the uighur medicine ASMq [39].…”
Section: Transforming Growth Factor-b Pathwaymentioning
confidence: 99%
“…It has been reported that peroxisome proliferator-activated receptor-γ (PPARγ) ligands, 15d-PGJ2 and GW7845, could inhibit the expression and phosphorylation of TGF-β1/Smads [18]. Either disruption or neutralization of TGF-β/Smads signaling by botulinum toxin type A, tetrandrine, baicalein, loureirin B, or the Uighur medicine ASMq can decrease the myofibroblast properties [19].…”
Section: Reviewmentioning
confidence: 99%